Domestic europeanization - institutional entrepreneurs and welfare state change - RECWOWE; Zirra, Sascha (Edinburgh, 2010)
"In this paper, we examine the domestic Europeanization of employment policy in two Continental countries — Germany and France. While both countries have experienced substantial labour market reforms in the last decade, the reform fields differ considerably. This paper argues that this is because the appropriation of European resources depends on the domestic patterns of bureaucratic co-ordination. Our analysis reveals that, in Germany horizontal co-ordination has fostered a discursive strategy of a unit in the labour ministry that contributed to the cognitive change towards activation. In France, centralistic co-ordination has blocked the labour ministry from substantial discursive strategy, but by a programmatic strategy it has contributed to improving existing schemes of insertion."